REQUIREMENTS, INFLUENCERS AND ENABLERS FOR MODELLING THE INTEGRATION OF PROJECT MANAGEMENT FOR IMPROVING CONSTRUCTION SITE MANAGEMENT PRACTICES FOR SMALL AND MEDIUM CONSTRUCTION COMPANIES - Bruno Sánchez (Journal of Architecture, Planning and Construction Management, 2019)
The need for tools to achieve a higher level of competitiveness and profitability has made management systems an important partner for construction companies. The environment in which construction projects are developed is dynamic, mainly characterized by complexity, uncertainty, interdependence, nonlinearity, ambiguity and speed. This research adopted a deductive reasoning in two phases: Literature Review and Interviews. The first phase was focused on underlying the crucial current issues that impact on Construction Site Management and the relationships among Project Management, Construction Site Management, Systems Thinking and Complexity Theory. The second phase was carried out so that practitioners validated the research result. The result of this study is a conceptual framework of requirements, influencers and enablers to support General Contractors in developing their Project Management Systems.